Examining the Ability to Solve Mathematical Problems of First–Year Secondary School Students through Polya’s Problem–Solving Process - Chanprom, Panprachan; Khum–un, Seree; Jirachotdaecho, Ghirana (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
The objectives of this study were to 1) compare the ability in solving mathematical problems on Graphs and Linear Relations for the First-Year Secondary School Students using problem solving process based on Polya Method and criteria; 2) compare the ability to solve math problems on Graphs and Linear Relations for the First-Year Secondary School Students before and after using a problem-solving process based on Polya Method, and 3) study the satisfaction of First-Year Secondary School Students towards learning management by using problem solving process based on Polya Method. Using the simple random sampling method, the researcher collected a sample consisting of 33 First-Year Secondary School Students at the Demonstration School of Ramkhamhaeng University (Secondary Division). The research instruments were to: (1) a mathematics ability test in solving mathematical problem test on Graphs and Linear Relation; (2) a questionnaire on the students’ satisfaction toward learning management based on Polya Method. The research results showed that: 1) the students’ ability to solve mathematical problems using the Polya-based problem solving process was higher than the criteria at the statistically significant level of .01; 2) the post-study achievement of First-Year Secondary School Students using the Polya-based problem solving process was higher than before-study at the statistically significant level of .01, and 3) the satisfaction of First-Year Secondary School Students with learning management using Polya’s conceptual problem solving process was at a high level.